Optimising Video Conferencing Tools for Educational Leadership: Enhancing Virtual Collaboration and Leadership Skills Development Theoretically - Adeoye, Moses Adeleke; I Wayan Widiana; Hasan Baharun; Imam Shofwan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
This research examines the optimisation of video conferencing tools (VCTs) to enhance virtual collaboration and leadership skills development in educational settings. The research problem focuses on how VCTs can effectively improve interactions among educators and foster essential leadership competencies. The research objectives include identifying best practices for VCT implementation, exploring their impact on leadership development and assessing the challenges institutions face. Utilising a qualitative research design, this research analyses existing literature and case studies to gather insights into using VCTs across various educational contexts. Data was collected through a comprehensive review of scholarly articles, reports and case studies that focus on the effectiveness of VCTs. Major findings indicate that optimised VCTs significantly enhance communication, foster collaboration, and contribute to developing vital leadership skills such as adaptability and emotional intelligence. The research also highlights barriers such as differing levels of technological proficiency and resource access, which can impede effective VCT implementation. In conclusion, the research emphasises the necessity of establishing clear communication protocols, providing ongoing professional development, and cultivating a collaborative culture to maximise the benefits of VCTs. By addressing these challenges and implementing best practices, educational leaders can leverage VCTs to create more engaging and inclusive learning environments, ultimately transforming educational leadership and collaboration in the digital era.